Assessing investment in manual handling risk controls: a scoring system for use in observational studies. Issue 1 (21st December 2004) - Smedley, J; Poole, J; Waclawski, E; Stevens, A; Harrison, J; Buckle, P; Coggon, D
Abstract : Most UK hospitals now have manual handling policies, but few studies have assessed their impact. To facilitate such research, a system for ranking the investment in manual handling risk controls was devised and applied to 109 acute hospitals in the UK. High scoring hospitals performed well on all aspects of manual handling risk management. Low scoring hospitals had a manual handling policy and recorded accidents and sickness absence, but had limited resource for expert manpower and equipment.